Reincarnation of Dalai lama’s in history of Tibetan Buddhism (Bodhi Path, 2020)
The institution of reincarnation (Tib. Trulku, sprul sku) is embedded in the Buddhist (and also hindu) concept of the cycle of birth, death and rebirth (Sanskr. Samsara), which applies to all conscious being until they attain Nirvana. According to the religious viewpoint of Buddhists, this cycle has no commencement and it is endless, while every sentient being passes from one existence to the other according to its moral behavior. Later, with the development of Mahayana Buddhism, the concept of ‘three bodies’ (sanskr. Trikaya) of Buddha Sakyamuni was formulated. According to the concept, the Buddhahood was described in terms of ‘bodies’ which represent various aspects of the Buddhahood: a) the true body of the Buddha (Sanskr. Dharamkaya) the eternal and cosmic body of the Buddha which embodies the supreme truth and transcends the form of physical and spiritual bodies; b) the ‘body of enjoyment’ (Sanskr. Sambhogakaya) this correspond to the forms of Buddha’s and bodhisattva in celestial realms and it can be perceived only by those a specific level of attainment; and c) ‘transformation body’ (Sanskr., Nirmanakaya, Tib. Trulku, chin, buofo) the material body in which Buddha’s and bodhisattvas appear to ordinary human being on their path towards the attainment of Nirvana1. The trikaya notion spread from India to Tibet from the 7th century as part of the Mahayana Buddhist teachings. In the late 10th and early 11th centuries, throughout the so-called ‘later dissemination’ (Tib. Phyi dar) of Buddhism in Tibet, a ‘Tibetanization’ of Buddhism started which was accompanied by the institutionalization of Buddhism in Tibetan society and the establishment of Tibetian Buddhist schools. As a part of that process of domestification of Indian religious ideas and philosophical concepts in Tibet, the institution of Buddhist reincarnations, trulkus, had emerged as a distinctive feature of the Tibetans Buddhist tradition.
Keywords: Reincarnation of Dalai lama; Tibetan Buddhism